The Effective Factors On Recievers\' Access To Health Care Services In Urban Health Care Centers - M Khayatan; AA Nasiri Pour; M Amini; SM Mohamad Nejad (Tehran University of Medical Sciences, 2011)
Background and Aim: In any country, one of the fundamental goals of health policymakers is to facilitate the people's access to treatment and health care services. Therefore, the aim of this study was to identify factors that influence recievers' access to delivered services in urban health care services. Materials and Methods: We performed this descriptive and cross sectional study in year 2008. We used the multi-stage sampling method for selecting 57 staffs of urban health care centers as statistical samples. The valid and reliable questionnaire for gathering data was designed. Data was analyzed by SPSS 2 version 13 software. Results: Our findings indicate that mean scores of individual, geographical, financial and structural factor was 2.29 (61.4% with high impact), 2.42 (57.9% with high impact), 2.27 (56.1% with high impact) and 2.58 (86% with high impact), respectively. (Our mean score range was 0 to 3). Conclusion: According to the assessment of employee's viewpoint of Urban Health Care Centers, all of four individual, geographical, financial and structural factors had high influence on person's access to health care services in Urban Health Care Centers. Consequently this study has presented suggestions (according to the findings) for improving access to delivered services in urban health care centers.